Comparison of the Euler-Bernoulli- and Solid Models of Three-Point Bending Test Specimens - Vadai, Zsolt (International Journal of Engineering and Management Sciences, 2021)
For hand calculations, the Euler-Bernoulli beam model has become widespread in engineering practice due to its simplicity and accuracy. In the present study, I compare the state variables calculated based on the Euler-Bernoulli model of a crack-free concrete beam and a crack-free concrete beam reinforced with FRP bars with the result of the three-dimensional solid body model.